Monoclonal antibody detects oligodendroglial cell surface protein exhibiting temporal regulation during development - Grzenkowski, Martina; Niehaus, Antje; Trotter, Jacqueline (Glia, 1999)
As tools to study stage-specific surface molecules expressed during the development of oligodendrocytes, we have generated monoclonal antibodies against peanut agglutinin (PNA)-binding glycoproteins isolated by affinity chromatography from the oligodendroglial precursor cell line Oli-neu. In this paper we report the characterization of the monoclonal antibody 7D10. The 7D10 antibody recognizes a 145-kD cell surface glycoprotein expressed by postmitotic multibranched cells of the oligodendroglial lineage. The antigen stains subpopulations of myelin-associated glycoprotein (MAG) and O4-positive cells and is subsequently down-regulated during further differentiation in vitro. The 7D10 antigen is also expressed by a subpopulation of astroglial cells but not by neurons. A truncated form of the protein is released by antigen-expressing cells into the culture supernatant.